A new social media conscious approach to Celebrity Translators: a case study of Italian influencer Francesca Crescentini aka Tegamini - Fini, Sylvia (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
This work aims at providing a different contemporary perspective on Celebrity Translators in the context of modern society immersed in social media and influencer culture. The main research question is can influencer translator Francesca Crescentini (Tegamini), a translator with an active of 56 published translations and more than 170,000 followers on Instagram, be defined as a Celebrity translator? I will answer this question looking at what she has in common with Celebrity Translators like Haruki Murakami, and what on the other hand is unique about her specific case. I will pay special attention to how she fulfils some of the features of celebrity translators through her use of social media, specifically how she uses it as paratext, as a way to be in touch with her public, as a marketing tool for her translations, and as a way to display her persona. Though Crescentini does not completely fit in the Celebrity Translator model proposed by Akashi, her visibility is especially surprising considering the Italian context, prone to translator erasure. That is why I believe she matches enough to be considered a Celebrity Translator, and possibly presents new elements for future reworkings of the definition.
Keywords: Literary Translation